Space and time bisection in schizophrenia - Martinez-Cascales, Isidro; De La Fuente, Juanma; Santiago, Julio; Santiago, Julio (Frontiers in Psychology, 2013)
As a test of the idea of a common brain system responsible for representing all prothetic dimensions, schizophrenic patients and healthy participants took part in a line bisection task and two visual temporal bisection tasks, one using durations from 1 to 4 seconds and another using 30 seconds long specially designed stimuli (aging faces). Against expectations, schizophrenics showed better precision (smaller variable error) both in line bisection and the aging faces temporal task than healthy controls. Moreover, patients also showed less bias (smaller constant error) than controls in the aging faces task. This increased precision correlated with degree of severity of schizophrenia. Although no group differences were found in the temporal task with shorter intervals, both variable and constant error measures correlated marginally with severity of schizophrenia, also in the direction of smaller error in more severe cases. Thus, overall, spatial and temporal tasks behaved similarly across groups. However, bias and precision indexes did not covary across the three tasks when correlations where computed over the whole set of participants in the present study. The results thus provide mixed support for a common system behind spatial and temporal processing and point towards the need of developing a more nuanced view of magnitude representation in the mind/brain.